Strategies for the management of conjunctive use of surface water and groundwater resources in semi-arid areas: a case study from Pakistan - Qureshi, Asad Sarwar; Turral, Hugh; Masih, Ilyas (International Water Management Institute, 2004)
Due to inadequate rainfall, groundwater has acquired a vital role in the development of Pakistan's agricultural economy. However, a lack of awareness concerning the use of groundwater, either by itself or combined with canal water, has added large amounts of salt to the soil. As a result, large tracts of irrigated lands are already salinized, while many others are under threat. This report presents the results of a modeling study carried out to evaluate the long-term effects of a different quality of irrigation water on root zone salinity. The simulations were performed for the Rechna Doab (sub basin of the Indus Basin) in Pakistan, by using 15 years of actual rainfall and climatic data.